Checking the genetic integrity of laboratory mice with the help of conventional methods (Journal of Laboratory Animal Science, 2019)
Animal models are well documented in the literature and are used for experimentation due to their specific  characters or response to the chemicals. Any deviation of these animals from the reported characters or  response renders the animal unsuitable for the research. Therefore, use of genetically defined laboratory  animal model is equally important to that of use of pure chemicals in any biomedical research. Procurement  of pure lines and their sustained maintenance in the animal facility is of utmost importance for the existence  and functioning of any animal facility. Keeping in view of the fact that despite careful and defined breeding  program, genetic contamination and strain alterations may occur. The present study was undertaken to  ascertain the genetic purity of strains of laboratory mice maintained at ACTREC. Skin grafting, coat colour  testing and seven biochemical markers were studied. The results of all these tests showed that the rodent  strains maintained at ACTREC have no genetic contaminations/ drift even after maintaining the strains for  as many as 136 generations. The data indicates that merely conducting these simple tests, it is possible to  establish in-house genetic quality control program and check the authenticity of the laboratory animals.
Keywords: genetic monitoring; mice; ACTREC